Enseigner une langue vivante étrangère à l'école (cycle 3) - Jacques Beaucamp (Recherches en didactique des langues et des cultures)
Foreign language learning is part of the primary curriculum in France today. In the upper primary classes, the choice of the communicative approach is widely advocated and, in hopes of reactivating the L1 acquisition process, most teachers favor implicit learning, and lots of exposure to linguistic input. In the language class this orientation results in a learning process which is based mainly on imitation and repetition. Our research aims at validating a more explicit approach, including conscious analysis of the target-language pronunciation system. such an approach may enable young learners to overcome the habits they have naturally acquired in their L1, to discover a new phonological system and to (re)construct meaning.